Pathways to positive youth development: Identifying family, school, and neighborhood influences on civic involvement in emerging adulthood - Mahatmya, Duhita (2011)
Guided by Bronfenbrenner's ecological theory of human development and social capital theory, this study examined the pathways that link childhood neighborhood assets, adolescent family and school social capital, and civic involvement in emerging adulthood. Three waves of data from the National Longitudinal Study of Adolescent Health (Add Health) and multi-level structural equation models were used to examine the hypotheses set forth in this study. Findings revealed that adolescent family and school social capital were shown to have unique influences on reports of civic involvement in emerging adulthood, and the effect of childhood neighborhood assets was mediated by the degree of family cohesion in the adolescents' home. Moreover, the expression of neighborhood, family and school pathways to civic involvement in emerging adulthood were found to differ by neighborhood groups, gender and race. These results help to illustrate the importance of examining multi-contextual influences on civic involvement in emerging adulthood. In addition, the results from this study can inform efforts to strengthen the theory of adolescent civic engagement and policies on how to educate youth and communities on civic engagement and its benefits